PENYIMPANGAN TERHADAP PERJANJIAN HIBAH ANTARA PERKAWINAN CAMPURAN DALAM KAITANNYA DENGAN PERAN NOTARIS (STUDI PUTUSAN PENGADILAN NEGERI DENPASAR NOMOR 723/PDT.G/2013/PN.DPS JO PUTUSAN MAHKAMAH AGUNG NOMOR 91 PK/PDT/2017) - Gladwin Lukman; Endang Pandamdari (Jurnal Hukum Adigama, 2020)
This research takes the formulation of the problem, namely whether the decision of the Denpasar District Court judge rejecting all claims to cancel the agreement between I Gusti Ayu Ita Dewi and Sven Hollingger as a wife partner is in accordance with the applicable legal provisions, and what is the role of the notary in making the grant deed in the form of land from I. Gusti Rai Tantra to I Gusti Ayu Ita Dewi who was handed back to Sven Hollingger who is a foreign national in the verdict. The results show that 1) The decision of the Denpasar District Court judge rejecting all claims for the cancellation of the grant agreement between I Gusti Ayu Ita Dewi and Sven Hollingger is not in accordance with the prevailing laws and regulations in Indonesia. 2) The role of the notary in drawing up the land grant deed from I Gusti Rai Tantra to I Gusti Ayu Ita Dewi which was handed over to her husband, which in reality means between husband and wife if prohibited because it is contrary to Article 1678. In the verdict between I Gusti Ayu Ita Dewi and Sven Hollingger, the notary in charge of making the grant deed did not apply the precautionary principle in carrying out actions because the deed did not contain material truth.